Generalized switched inductor cell multilevel converter - Chauhan A.K.; Raghuram M.; Singh S.K. (My University, 2025)
Z-source inverters are very popular in recent times because of their inherent capability to step up/down the input voltage. This concept can be extended to multilevel inverter. As compared to multilevel inverter, two level Z-source inverter has several drawbacks like high filter size, poor performance in terms of THD, efficiency etc. This paper presents a Z-source integration into modular multilevel converter. Switched inductor cells are used as Z-source network because they exhibit better flexibility and reduced passive element count to achieve desired gain. Furthermore, the analysis of proposed inverter is done in discontinuous current mode(DCM) which signifies that even higher gain can be achieved as compared to continuous current mode(CCM). To implement the control scheme full shoot through or upper shoot through/ lower shoot through technique are developed and compared. For performance calculation, the proposed inverter is simulated using MATLAB/Simulink platform. © 2017 IEEE.